Board Attributes and Foreign Shareholdings in Listed Firms in Nepal Stock Exchange - Chawal, Cristina; Regmi, Degendra; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2025)
This study examines the relationship between board attributes and foreign shareholdings in Nepal stock exchange. Return on equity, return on assets and foreign shareholding are selected as the dependent variables. Similarly, board size, board meeting, board diversity, foreign ownership, board independence and audit committee and are selected as the independent variables. The study is based on secondary data of 13 commercial banks with 104 observations for the period from 2015/16 to 2022/23. The data were collected from Banking and Financial statistics published by Nepal Rastra bank and the annual reports of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the potential of bankruptcy in Nepalese commercial banks. The study revealed that audit committee has a positive impact on return on assets and return on equity. It means that increase in audit committee leads to increase in return on assets and return on equity. Likewise, audit committee has a negative impact on foreign shareholder. It means that increase in audit committee leads to decrease in foreign shareholder. Likewise, board size has a positive impact on return on assets and return on equity. It means that increase in board size leads to increase in return on assets and return on equity. Likewise, board size has a negative impact on foreign shareholder. It means that increase in board size leads to decrease in foreign shareholder. Furthermore, board diversity has a negative impact on return on assets and return on equity. It means that increase in board diversity leads to decrease in return on assets and return on equity. Likewise, board diversity has a positive impact on foreign shareholder. It means that increase in board diversity leads to increase in foreign shareholder. Similarly, board meeting has a negative impact on return on assets and return on equity. It means that increase in board meeting leads to decrease in return on assets and return on equity. Likewise, board meeting has a positive impact on foreign shareholder. It means that increase in board meeting leads to increase in foreign shareholder. Similarly, foreign ownership has a positive impact on return on equity. It indicates that increase in foreign ownership leads to increase in return on equity. Likewise, foreign ownership has a negative impact on return on assets and foreign shareholder. It indicates that increase in foreign ownership leads to decrease return on assets and foreign shareholder. Moreover, this study showed board independence has a negative impact on return on equity. It means that increase in board independence leads to decrease in return on equity. Likewise, board independence has a positive impact on return on assets and foreign shareholder. It shows that higher the board independence, higher would be return on assets and foreign shareholder.